Role of salivary miRNAs in the diagnosis of gastrointestinal disorders: a mini-review of available evidence - Săsăran, Maria Oana; Bănescu, Claudia (Frontiers in Genetics, 2023)
MiRNAs are short, non-coding RNA molecules, which are involved in the regulation of gene expression and which play an important role in various biological processes, including inflammation and cell cycle regulation. The possibility of detecting their extracellular expression, within body fluids, represented the main background for their potential use as non-invasive biomarkers of various diseases. Salivary miRNAs particularly gained interest recently due to the facile collection of stimulated/unstimulated saliva and their stability among healthy subjects. Furthermore, miRNAs seem to represent biomarker candidates of gastrointestinal disorders, with miRNA-based therapeutics showing great potential in those conditions. This review aimed to highlight available evidence on the role of salivary miRNAs in different gastrointestinal conditions. Most salivary-based miRNA studies available in the literature that focused on pathologies of the gastrointestinal tract have so far been conducted on pancreatic cancer patients and delivered reliable results. A few studies also showed the diagnostic utility of salivary miRNAs in conditions such as esophagitis, esophageal cancer, colorectal cancer, or inflammatory bowel disease. Moreover, several authors showed that salivary miRNAs may confidently be used as biomarkers of gastric cancer, but the use of salivary miRNA candidates in gastric inflammation and pre-malignant lesions, essential stages of Correa’s cascade, is still put into question. On the other hand, besides miRNAs, other salivary omics have shown biomarker potential in gastro-intestinal conditions. The limited available data suggest that salivary miRNAs may represent reliable biomarker candidates for gastrointestinal conditions. However, their diagnostic potential requires validation through future research, performed on larger cohorts.